A double blind trial of sulpiride in Huntington's disease and tardive dyskinesia. Issue 8 (August 1984) - Quinn, N; Marsden, C D
Abstract : Eleven patients with Huntington's disease and nine patients with tardive dyskinesia participated in a randomised double-blind crossover trial of sulpiride (as sole antidopaminergic therapy) versus placebo. Although functional improvement was not seen in Huntington's disease patients, sulpiride reduced movement count and total dyskinesia score in both conditions. Sulpiride differs pharmacologically in several respects from conventional neuroleptics, and has not been convincingly shown to cause tardive dyskinesia. Among currently available treatments, it may therefore be considered a drug of choice for treatment of tardive dyskinesia.